Estimation of Bouguer correction density based on underground and surface gravity measurements and precise modelling of topographic effects – two case studies from Slovakia - ZAHOREC, Pavol; PAPČO, Juraj (Contributions to Geophysics and Geodesy, 2018)
We present a simple and straightforward method for estimating the meandensity of topographic masses based on underground gravity measurements along with topography modelling. Two examples under different conditions are given, the first coming from a railway tunnel passing through a Mesozoic karst area and the second from an active coal mine situated in a Neogene sedimentary basin. Relative gravity measurements were processed and corrected by topographic effect modelling based on high-precision airborne LiDAR-derived elevation models. In addition, detailed mining tunnel gravimetric modelling based on terrestrial laser scanning data is presented. Resulted mean (bulk) densities are compared with those obtained from detailed surface gravity measurements as well as with available rock-samples density analysis.